Principal’s Leadership of School in Empowering Computer-Based Teachers at SD Surakarta - Maryani, Dwi; Cholidah, Nur; Retno, Andriani Chondro; Murtiyasa, Budi; Masduki, Masduki; Sutama, Sutama; Sumardjoko, Bambang; Haryanto, Sigit (Graduate Program Magister Manajemen Pendidikan, 2024)
In the era of the Industry 5.0 revolution, learning is transformed by the digitalization of education. The background of this research is the very rapid development of computing in education, which requires the use of educational software and human resources (SDM). This involvement will have an impact on students in learning at Madrasah Tsanawiyah Surakarta. Qualitative research methods were used with a case study approach by subject research teachers and students of the Seventh Grade Madrasah Tsanawiyah Surakarta. Data collection techniques include documentation, observations, and interviews. Analysis techniques using triangulation of sources, methods, and techniques. Research results show that students are involved through technology in digital classroom collaboration by creating teaching materials using applications, viewing students on computer screens, and making computational-based questions. Implementation of digital use to maintain teachers currently has not been collaborative. Teacher understanding with discussions, workshops using innovative LCD learning processes with facilities, Flip Books, and one-month workshop positions inside the school. The researchers’ findings show that the use of digital media is very helpful in developing student understanding; students are more actively following learning as well. Contributing to teachers’ creation of Flip Books as a learning module.